PENGARUH OPTIMALISASI RUANG PUBLIK SENTRA KULINER TERHADAP PEMBENTUKAN KARAKTER DAN INTERAKSI SOSIAL MASYARAKAT (STUDI KASUS DI DESA CIPAGALO KABUPATEN BANDUNG PROVINSI JAWA BARAT) - Santi Salayanti; Vany Octaviany; Syarip Hidayat (Journal of Innovation Research and Knowledge, 2026)
Abstract: Cipagalo Village is located in Bojongsoang District, Bandung Regency, West Java. This village has strategic regional characteristics because it is close to the center of Bandung, making it potential for development as a tourist village based on local wisdom and creative economy. There are public spaces located in Cipagalo Village that have an important role in building social interaction and strengthening the character of the community. It is necessary to analyze the influence of the optimization of public space in the Culinary Center on the formation of the social character of the people of Cipagalo Village. The market has an important role in the local economy as a center for transactions and social interaction of the community. However, in Cipagalo Village, the traditional market still faces various challenges, such as suboptimal accessibility, limited facilities, and low quality of the products offered. This community service program aims to design a modern market design that not only improves accessibility for the community, but also supports the improvement of the quality of local products. The approach used involves participatory studies with local communities to understand their needs, habits, and expectations of the ideal market. The proposed design concept prioritizes a friendly layout for all community groups, the provision of adequate sanitation facilities, and the integration of technology to improve transparency and efficiency of product distribution. In addition, the program also emphasizes the importance of social interaction in market management through training for traders and the public regarding healthy and sustainable trading practices. The results of this community service activity are expected to be able to create a more inclusive modern market, increase the competitiveness of local products, and strengthen the economy of the people of Cipagalo Village. With the existence of a modern market based on social interaction, it is hoped that a more dynamic and sustainable economic ecosystem will be formed for all stakeholders. The Culinary Center as a culinary center is also a forum for the community to participate in community-based economic activities, which strengthen social values and social attachment. A well-managed public rang is able to positively shape the social character of the community, improve the quality of life, and strengthen the local identity of Cipagalo Village. Therefore, the active role of the government and the community is needed in maintaining and developing public space as a means of sustainable social development. This research shows that the optimization of the Culinary Center, both in terms of facilities, governance, and social activities held, has a positive impact on social cohesion, a sense of togetherness, and the values of community mutual cooperation. People who actively use public spaces show an increase in communication between citizens, participation in social activities.